The three little vampires - Adams, Georgie (Great Britain 2015)
Meet the Three Little Vampires, Verity, Vikki and Vaz! They're planning a SPOOKY Hallowe'en party - but will the villainous Count Bagel's tricks stop the fun? Can the clever Little Vampires save the night, and will everyone be able to have a good time after all?